Shedding Light on the Formation and Structure of Kombucha Biofilm Using Two-Photon Fluorescence Microscopy - Tran, Thierry; Grandvalet, Cosette; Winckler, Pascale; Verdier, François; Martin, Antoine; Alexandre, Hervé; Tourdot-Maréchal, Raphaëlle (Frontiers in Microbiology, 2021)
Kombucha pellicles are often used as inoculum to produce this beverage and have become a signature feature. This cellulosic biofilm produced by acetic acid bacteria (AAB) involves yeasts, which are also part of kombucha consortia. The role of microbial interactions in the de novo formation and structure of kombucha pellicles was investigated during the three days following inoculation, using two-photon microscopy coupled with fluorescent staining. Aggregated yeasts cells appear to serve as scaffolding to which bacterial cellulose accumulates. This initial foundation leads to a layered structure characterized by a top cellulosic-rich layer and a biomass-rich sublayer. This sublayer is expected to be the microbiologically active site for cellulose production and spatial optimization of yeast-AAB metabolic interactions. Pellicles then grow in thickness while expanding their layered organization. Comparison with pellicles grown from pure AAB cultures shows differences in consistency and structure that highlighting the impact of yeasts on kombucha pellicles’ structure and properties.